2008
DOI: 10.1007/s10494-008-9176-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sudden Expansion on Entrainment and Spreading Rates of a Jet Issuing from Asymmetric Nozzles

Abstract: Turbulent free jets issuing from five different nozzle geometries; smooth pipe, contracted circular, rectangular, triangular, and square, are experimentally investigated by using TSI 2-D laser Doppler velocimetry (LDV) to assess the effect of nozzle geometry and quarl (i.e. a cylindrical sudden expansion) on jet entrainment and spreading. The centerline mean velocity decay and the jet half-velocity width, which are indicators of jet entrainment and spreading rates, are determined for each nozzle's flow configu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 32 publications
0
10
2
Order By: Relevance
“…From a literature survey, previous studies were conducted on the turbulent flow of a jet issuing from differrently shaped nozzles [1][2][3][4][5]. From their results, it was found that the near-field flow of the jet is strongly influenced by the three-dimensional structure dependent on the loss of axisymmetric nature.…”
Section: Introductionmentioning
confidence: 99%
“…From a literature survey, previous studies were conducted on the turbulent flow of a jet issuing from differrently shaped nozzles [1][2][3][4][5]. From their results, it was found that the near-field flow of the jet is strongly influenced by the three-dimensional structure dependent on the loss of axisymmetric nature.…”
Section: Introductionmentioning
confidence: 99%
“…To the best knowledge of the present authors, all published literature addressed a central jet issuing from a circular pipe surrounded by an annulus of swirling air. Recent studies summarized in Iyogun and Birouk (2008, 2009a, 2009b have shown that asymmetric fuel nozzles have the potential of inducing various turbulent structures compared to a simple pipe counterpart. Therefore, the main purpose of the present study was to examine some of the stability features of non-premixed swirling flame as subjected to both large scales induced by the swirl and relatively smaller scales generated by the asymmetric fuel nozzle.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent development showed that noncircular injectors would enhance further the mixing process between a jet and its surroundings. Pertinent literature has recently been briefly reported in, for example [1,2]. These recent studies, indeed, revealed that the use of such passive control methods can in fact lead to increasing mixing between a jet and its surrounding medium.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that these vortex pairs can have a significant impact on jet mixing [5]. Another recently proposed passive method for increasing jet mixing and spreading uses a collar, which is a sudden expansion of the nozzle [1,[16][17][18][19]. Husain et al [16] studied an elliptic whistler (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation